(untitled) (Academicia Globe: Inderscience Research, 2021)
This article describes the competence of a preschool educator in a broad and comprehensive way, and provides personal opinions and recommendations based on the views and opinions of pedagogical scientists and thinkers. The educator must first be educated, know the great life in which he lives, understand the laws of nature and society, be socially active, master the pedagogy of general and preschool education, the psyche and physiology of children, and know the age characteristics of children. The educator plays a special role in shaping the child’s personality. In particular, it is required that each child be responsible for his or her formation as an individual.